Analysis Of The Effect Of Macroeconomic Variables On Returns Of Mutual Fund Shares Traded At State Owned Bank - Alfiana Alfiana; Petrus Loo; Loso Judijanto; Jemmy Christian Rakinaung; Ngurah Pandji Mertha Agung Durya (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The purpose of this study is to determine whether IHSG, inflation, exchange rates, and BI rates have a meaningful impact on stock mutual fund returns. Panel data is the secondary data used in this quantitative research design. The population under investigation consists of stock mutual funds that are published and registered with OJK. Purposive sampling was the method of sampling that was employed. Secondary data (found online) and library research were the methods of data collection used in this study. A panel data regression test is the research methodology employed in this study. The analysis that was conducted yielded the following conclusions, which can be drawn: The panel data regression test results indicate that returns on stock mutual funds are significantly impacted by the IHSG, inflation, exchange rate, and BI rate all at the same time. IHSG has a demonstrably positive impact on stock mutual fund returns, according to the findings of the partial panel data regression test. It has been established that returns on equity mutual funds are significantly impacted negatively by inflation. It has been demonstrated that returns on stock mutual funds are significantly positively impacted by exchange rates. It has been demonstrated that stock mutual fund returns are significantly impacted negatively by the BI rate.